Implementation of Scaffolding Techniques in Early Childhood Learning to Improve Numerical Skills - Reni Rohani; Soni Samsu Rizal; Saeful Millah (Journal of Asian Primary Education (JoAPE), 2025)
This research is motivated by the low numerical skills of early childhood who still often have difficulty in recognizing numbers, counting concrete objects, and understanding the concept of simple quantities. Numerical skills are important for children to master early because they are the basis for learning mathematics at the next level. Therefore, appropriate learning strategies are needed and according to the stage of Child Development. This study aims to describe the implementation of Scaffoding techniques in mathematics learning in order to improve the numerical skills of children in KB Miftahul Huda. The research method used is Class Action Research (PTK) with two cycles. The study subjects consisted of 15 children of Group B aged 5-6 years. Scaffolding techniques are applied through gradual assistance in the form of teacher directions, lighter questions, demonstrations with concrete media, and slowly reducing assistance according to the child's ability. Data were collected through observation, interviews, and documentation, and then analyzed qualitatively and quantitatively. The results showed a significant improvement in children's numerical skills. In the pre cycle only 33% of children were able to count objects and match numbers with numbers. After the application of scaffolding in the first cycle increased to 46%, and in the second cycle reached 86%. It is proved that scaffolding technique is effective in improving early childhood numerical skills. This strategy is not only relevant to the theory of child development, but also makes a real contribution to the practice of learning in early childhood, especially in building a concrete and gradual understanding of numbers.